Performance Of Manghatahon Sijagaron Saurmatua Batak Toba Anthropolinguistic Approach - Simangunsong, Reka; Sibarani, Robert; Perangin-angin, Alemina Br (International Conference on Sciences Development and Technology, 2022)
This study aims to find out the text, cotext and context of MSS tradition in the BT community, describe the performance of the text, co-Text and context, explain the reasons for the use of Sijagaron saurmatua by the BT community. The method used is descriptive qualitative with an ethnographic approach to find and understand in depth an event of a cultural phenomenon. The research data is in the form of speech performance data or in the form of lingual text from informants through interviews. The results of the study found 14 elements used in Sijagaron saurmatua. An assertive speech act that functions to express the speaker's psychological attitude towards a situation by making suggestions (suggesting). Expressive speech acts that function to express the speaker's psychological attitude towards a state of appreciation (appreciating) and directive speech acts in which the speaker takes an advising action. And the commissive speech act is an expression of prayer (praying) with the function of kinesis speech, material, and traditional clothing. Context is in the form of ideological, social, cultural, and situational contexts. The meaning contained is a form of gratitude, fortune, and honor. Speech functions consist of expressive functions, directive functions, declarative functions, and commissive functions. The cultural function contained is as a form of entertainment, a means of validating cultural institutions and as an educational tool. Values and Norms, namely religious values, logical values, ethical values, aesthetic values and norms contained in the form of norms of decency, law, custom, and customary norms. Local wisdom is in the form of social solidarity and mutual cooperation, kinship, mutual respect, gratitude, cultural preservation and harmony. The use of Sijagaron saurmatua in BT society is part of the reflection of human life on nature. Nature provides many benefits for humans, such as food, traditional medicine and convenience for other aspects.